Varicella zoster virus DNA exists as two isomers. - Ecker, J R (1982)
Fragments of varicella zoster virus DNA produced by EcoRI endonuclease cleavage were cloned in vector pACYC 184 and those produced by HindIII cleavage were cloned in pBR322. Restriction enzyme cleavage maps established by double digestion and blot hybridization showed that varicella zoster virus DNA has a Mr of 80 +/- 3 x 10(6) and exists as a population of two isomers.